From Colossal to Zero: Controlling the Anomalous Hall Effect in Magnetic Heusler Compounds via Berry Curvature Design - Manna, Kaustuv; Muechler, Lukas; Kao, Ting-Hui; Stinshoff, Rolf; Zhang, Yang; Gooth, Johannes; Kumar, Nitesh; Kreiner, Guido; Koepernik, Klaus; Car, Roberto; Kuebler, Juergen; Fecher, Gerhard H.; et al. (Physical Review X, 2018)
Since the discovery of the anomalous Hall effect (AHE), the anomalous Hall conductivity (AHC) has been thought to be zero when there is no net magnetization. However, the recently found relation between the intrinsic AHE and the Berry curvature predicts other possibilities, such as a large AHC in noncolinear antiferromagnets with no net magnetization but net Berry curvature. Vice versa, the AHE in principle could be tuned to zero, irrespective of a finite magnetization. Here, we experimentally investigate this possibility and demonstrate that the symmetry elements of Heusler magnets can be changed such that the Berry curvature and all the associated properties are switched while leaving the magnetization unaffected. This enables us to tune the AHC from 0 Ω-1 cm-1 up to 1600 Ω-1 cm-1 with an exceptionally high anomalous Hall angle up to 12%, while keeping the magnetization the same. Our study shows that the AHC can be controlled by selectively changing the Berry curvature distribution, independent of the magnetization.
CRIS-Team Scopus Importer:2022-04-14